Perancangan Sistem Deteksi Dini Bencana Banjir Menggunakan Teknik Pengiriman DTMF Berbasis Modul RF 433 Mhz Dan Arduino - M. Zainal Arifin; Ema Utami; Eko Pramono (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
Flood is one of the unpredictable natural disasters, especially in the rainy season. There are many effects for many people, such as they lose their property and sometimes have many victims due to floods. So that, estimation of water level is important to detect the basic risk of flooding. In this study used the Water Level (TMA) in form of a short message technique which is can be sent from radio waves and river water level sensors. The value of the sensors to know the highest river water level itself, so it does not need signals, internet networks and also pulse for it. The final result of this study is the water level information which is normal status, standby I, standby II, standby III or standby IV.Keywords: RF 433MHz, Flood, Arduino, Early Detection